Millennials' Future Homeownership and the Role of Student Loan Debt. (28th August 2020) - Mountain, Travis P.; Cao, Xiang; Kim, Namhoon; Gutter, Michael S.
Abstract : The financial burden of student loans on individuals in the Millennial generation is a serious issue. We investigated the effect this financial burden has on not only current homeownership but also the expectations and timing for future homeownership. The data came from the 2016 UF/VT Millennial Housing and Student Debt Survey of 1, 327 young adults aged 19 to 35. We used a logistic regression model to determine differences in current homeownership and a two‐stage Cragg model to examine the expectation and timing of future homeownership. We found that while student loans negatively affected Millennials' current ownership rates, the Millennials still wanted to be homeowners. Moreover, the homeownership timeline for Millennials with student loan debt will be delayed by several years relative to their counterparts without student loan debt.